In situ and ex situ variability of phenological and morphological features in Caltha palustris L. under the conditions of the West Siberian forest steppe - Т. I. Fomina (Труды по прикладной ботанике, генетике и селекции)
Background. Caltha palustris L. is known as a medicinal, food, and ornamental plant. It is a circumboreal species, and hygrohelophyte. Due to its ecological specificity, this plant can be used to study the response to an abrupt change in environments. The goal was to assess the variance in phenological and morphological features of C. palustris in the forest steppe of Western Siberia.Materials and methods. Phenotypic characters of the native population and the accessions introduced from Kemerovo Province and Altai Territory were studied. Phenological observations followed a well-known technique for herbaceous perennials. Morphometric data were processed in the PAST program using statistical indicators: the arithmetic mean with an error (M ± mM), minimum and maximum values of the trait (lim), and coefficient of variation (Cv). Significance of differences was assessed using Student’s t-test (Pt) at a 5% significance level. For traits deviating from the normal distribution, the significance of differences was assessed using the Mann–Whitney criterion (PMW) by median values of the trait (Me) at the same 5% level.Results and conclusions. The accessions varied significantly in the timing and duration of phenophases. Plants in the native population grew later and bloomed for a long time because of the variation in microconditions. Ex situ plants produced the second generation of rosette shoots and were capable of long vegetating, but the Altai accession differed in later growth and shorter phenophases. All accessions significantly differed in morphological characteristics of the shoot, except for flower size. The introduced accessions were inferior to the native ones in shoot height, leaf size, and number of flowers due to non-optimal cultivation environments. Since C. palustris demonstrated high individual and interpopulation variability, it is promising to study this species in different natural populations and select the most ornamental and sustainable accessions.